The impact of the Wingate test on anaerobic power in the lower limbs of athletes with varied duration and load - Liu, Ying; Yan, Juntao; Gong, Zhigang; Liu, Qi (Frontiers in Physiology, 2025)
IntroductionThis study investigates the effects of Wingate anaerobic test (WAnT) on anaerobic capacity (AC) at different duration (20, 30, 40, 45 s) and resistance load (7.5%Body Mass (BM), 8.5%BM, 9.5%BM, 10.5%BM).Methods12 male runners of 200, 400 m were subjected to four WAnT of different durations and loads. The changes of AC and lower limb muscle characteristics were analyzed by WAnT and electromyography.ResultsThe result shows that the integrated of electromyography (lEMG), root mean square% (RMS%), mean power frequency (MPF) and AC of lower limb muscles of rectus femoris (RF), biceps femoris (BF), vastus medialis (VM), vastus lateralis (VL), tibialis anterior (TA) and peroneus longus (PL) were increased by duration (P < 0.05 or P < 0.01), but there was no significant difference in lEMG of MG (P > 0.05). Load significantly increased AC, IEMG, RMS% and MPF of lower limb muscles (P < 0.01). The interaction effect of duration and load had no significant difference on PP, MP, IEMG, RMS% and MPF (P > 0.05), but increased on Fl (P < 0.05).DiscussionIn conclusion, for 200 m and 400 m athletes, it is recommended to use a combination of 20 s and 10.5%BM load to achieve optimal peak power, as well as a combination of 20 s and 9.5%BM load for better average power. Different combinations of duration and load can be selected during the test to assess the corresponding capability.